2014
DOI: 10.1111/jiec.12089
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment and Service Life Prediction

Abstract: Models of buildings in life cycle assessment (LCA) often use simple descriptions of operational energy, maintenance, and material replacement. The scope of many building LCAs is often limited and uses assumptions such as building lifetimes of 30 to 50 years. In actuality, building lifetimes vary considerably, and scenarios using standard assumptions may have incorrect results. Assumptions concerning material replacement, repair, and maintenance should be deliberate and as realistic as possible. This research w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Therefore, it should be noted that as a result of the diversity of the methodologies used in the case studies and literature, the individual cases cannot be used to quantify reductions in general, but instead, illustrate the potential of different reduction strategies in various contexts. [42] Light weight construction CZ2, [43] NO4 [44], [39] NO2 [45] Optimising building form and design of lay-out plan SE4 [25] SE3 [28] NO1 [46] Building/service life extension SE7 [26] DK3a,b [47], [48] Element level analyses: [49], [50] JP4 [51] DK1 [52] Reusing building structures No comparative studies, but related Annex 57 case studies include UK12, DK1, SE7, CH1-5, CH8-9, CH11-13, AT4, [53] Flexible/adaptable design DK3c [47] SE6 [54] UK8 [55], UK11 [41], [56] Reducing construction stage impacts UK3, SE7 [26] UK5 [29], [57], [34] UK7 [33] Reducing end-of-life impacts [58] UK7 [33] 3…”
Section: Figure 1 Building Life Cycle Stages and Modules Included Inmentioning
confidence: 99%
“…Therefore, it should be noted that as a result of the diversity of the methodologies used in the case studies and literature, the individual cases cannot be used to quantify reductions in general, but instead, illustrate the potential of different reduction strategies in various contexts. [42] Light weight construction CZ2, [43] NO4 [44], [39] NO2 [45] Optimising building form and design of lay-out plan SE4 [25] SE3 [28] NO1 [46] Building/service life extension SE7 [26] DK3a,b [47], [48] Element level analyses: [49], [50] JP4 [51] DK1 [52] Reusing building structures No comparative studies, but related Annex 57 case studies include UK12, DK1, SE7, CH1-5, CH8-9, CH11-13, AT4, [53] Flexible/adaptable design DK3c [47] SE6 [54] UK8 [55], UK11 [41], [56] Reducing construction stage impacts UK3, SE7 [26] UK5 [29], [57], [34] UK7 [33] Reducing end-of-life impacts [58] UK7 [33] 3…”
Section: Figure 1 Building Life Cycle Stages and Modules Included Inmentioning
confidence: 99%
“…In addition, the accelerated tests are quite expensive. There are also some other approaches to predict SL by considering service life models and obsolescence factors [1,34]. This method can be used for existing buildings or to be built buildings with the same material.…”
Section: Authormentioning
confidence: 99%
“…Life cycle assessment (LCA) studies that have been conducted, to date, consider the service life of building and building components between 30 and 70 years with a most commonly used value of 50 years (Table 1). However, the real picture is quite contradictory to these assumptions as the service life of buildings varies with materials, operation and maintenance and the surrounding environment [1,2]. This discrepancy may lead to inaccuracy of LCA analyses, and material and energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Research from the building and construction industry identified eight major factors that influence the cost and schedule of a project (new and renovation) [7,30,31]: Complexity of the building, technological requirements, project information, project team requirements, contract requirements, project duration, market requirements, and site requirements. Among those eight factors, three factors are particularly essential to a renovation project with an aim to achieve net zero: Complexity, technological requirements, and site requirements.…”
Section: Sensitivity Analysismentioning
confidence: 99%